Phenol Resin-Based Activated Carbon Fibre Catalytically Gasified by Potassium Hydroxide - Jin, Hangkyo; Ahn, Hyoseong; Kim, Tae-Kyung; Park, Hee-Moon; Chang, Bong-Jun; Kim, Jeong-Hoon (Asian Journal of Chemistry, 2012)
Phenol resin-based activated carbon fibre could be prepared at 973 K by catalytic activation using potassium hydroxide. Phenol resin fibre was impregnated with ethanolic solution of potassium hydroxide, carbonized and activated at 973 K, resulting in activated carbon fibers with different porosities. The potassium hydroxide accelerated the activation of the fiber catalytically to form narrow micropore preferentially in carbon dioxide atmosphere. The narrow micropore volume of 0.3-0.4 cc/g, total pore volume of 0.3-0.8 cc/g, mean pore width of 0.5-0.7 nm was obtained in the range of 20-50 % burnoff.